The role of teacher support in increasing youths’ intentions to disclose cyberbullying experiences to teachers - Nagar, Pooja Megha; Talwar, Victoria (Computers and education, 2023)
The current research on teacher support strategies for students who have been cyberbullied is inconsistent, which contributes to both teacher inaction and cyber-victims’ non-disclosure. Thus, the current study aims to address this issue of non-disclosure by measuring adolescents' intent to disclose hypothetical cyberbullying experiences to a teacher after being presented with cyberbullying vignettes. One-hundred and five adolescents between the ages of 12-to-17 years old (60% self-identified as Female; Mage = 14.26; SD = 1.51) participated. The vignettes followed a 5 × 4 within subject design to depict different types of support (No Support, Emotional, Appraisal, Informational, Instrumental) across different cyberbullying forms (Verbal, Visual, Exclusion, Impersonation). This study also aims to examine how self-reported perceptions of school climate influences disclosure intentions after being provided with support. Several multiple regression analyses were conducted to identify predictors of intentions to disclose. The results found that each support type increased intent to disclose in comparison to no support. Disclosure intentions increased when teacher support was provided for severe cyberbullying incidents, but disclosure intentions decreased when teacher support was provided for less severe cyberbullying incidents. Furthermore, disclosure intentions are higher among those who identify as female and have higher school climate scores. These findings highlight how the House (1981) framework can be applied to increase adolescents' intentions to disclose cyber-victimization experiences to their teachers, which has the potential to break the cycle of non-disclosure observed in youth, increase teacher competency to intervene, and boost adolescents’ confidence in their teachers. •Adolescents had high disclosure intentions in teacher support conditions•Adolescents did not show a preference for a specific type of teacher support•Disclosure intentions for severe cyberbullying increased with teacher support•Disclosure intentions for less severe cyberbullying decreased with teacher support•Disclosure intentions increased with strong school climate and support